Wednesday

April 16, 2014

April 16, 2014

Posted by **armut** on Wednesday, September 26, 2012 at 1:34pm.

- diffrential -
**Steve**, Wednesday, September 26, 2012 at 2:57pmsince 2 = e^ln2

e^(-kt) = e^(ln2 * -kt/ln2)

= (e^ln2)^(-kt/ln2)

= 2^(-kt/ln2)

**Related Questions**

Maths - P=(2J+1)exp(-(BJ(J+1))/kT) where B, k and T are constants a. Show that ...

Maths - Transform the following relationships/funtions into linear form and ...

Calculus II - What is sin(i) -- (sin of the imaginary number, i) What is cos(i...

calculus - Put the function P=40(39)t in the form P0e^kt. When written in this ...

diffrential equations - Find two linearly independent power series solutions to ...

Math/Calculus - How would I evaluate the following integral by using integration...

(expi)^i - This question is not well defined. By 'expi' do you mean exp(i)? In ...

Math - Rearrange for J; n=(2J+1)exp(-(BJ(J+1))/(KT)) where T, B and K are ...

Maths - Rearrange for T and J; n=(2J+1)exp(-(BJ(J+1))/(KT)) where B and K are ...

maths-complex numbers - by using the substitution w = z^3, find all the ...